Redesain Pengisian Jabatan Menteri Dalam Sistem Presidensial Di Indonesia - Yanto, Andri; Nugraha, Harry Setya (Fakultas Hukum Universitas Bangka Belitung, 2021)
The filling of ministerial positions in the presidential government system must be based on the pleasure of working and not because of political considerations or imbalances in the support of the President's groups or political parties. In fact, the filling of ministerial positions in Indonesia has so far been carried out using a political approach. The methodology used is a normative juridical research method, with a statutory and conceptual approach. The results of the discussion and conclusions of this study are first, the minister's task load is a lot of political dynamics; secondly, the filling of ministerial positions does not occur democratically; and third, new design ideas in filling ministerial positions include the requirements needed to be appointed as ministers, affirmation of the limitation of concurrent positions, and must first conduct a fit and proper test.